2016
DOI: 10.1186/s13148-016-0272-8
|View full text |Cite
|
Sign up to set email alerts
|

Methylome analysis for spina bifida shows SOX18 hypomethylation as a risk factor with evidence for a complex (epi)genetic interplay to affect neural tube development

Abstract: BackgroundNeural tube defects (NTDs) are severe congenital malformations that arise from failure of neurulation during early embryonic development. The molecular basis underlying most human NTDs still remains largely unknown. Based on the hypothesis that folic acid prevents NTDs by stimulating methylation reactions, DNA methylation changes could play a role in NTDs. We performed a methylome analysis for patients with myelomeningocele (MMC). Using a candidate CpG analysis for HOX genes, a significant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Global DNA methylation difference between the low and the high prenatal anxiety group was assessed. We compared DNA methylation of all long interspersed nuclear element (LINE) repeats by analyzing preprocessed and normalized beta values at CpG probes in both LINE-1 and LINE-2 repeats extracted from the HM450 data as described previously [ 30 ]. This analysis involved 15,612 CpG probes at LINE repeats localized throughout the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Global DNA methylation difference between the low and the high prenatal anxiety group was assessed. We compared DNA methylation of all long interspersed nuclear element (LINE) repeats by analyzing preprocessed and normalized beta values at CpG probes in both LINE-1 and LINE-2 repeats extracted from the HM450 data as described previously [ 30 ]. This analysis involved 15,612 CpG probes at LINE repeats localized throughout the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Buprenorphine exposure was associated with significant downregulation of miR-196a and miR-196b. Multiple predicted and/or validated target genes of miR-196a and miR-196b have been associated with developmental disorders (ZMYND11 72 for autism 73,74 and intellectual disability 75 ; HOXB7 76 for Huntington's disease 77 and neural tube defects 78,79 ). Other targets of downregulated miRs in opioid cases also have a role in opioid addiction (AQP4, 80,81 NR2C2 82 ) and co-dependence of alcohol and nicotine (NR2C2 83 ).…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 99%
“…A review showed support that a wide variety of environmental factors (e.g., chemical pollutants, diets, temperature changes, and external stresses) can contribute to long‐lasting effects on establishment and maintenance of epigenetic modifications that could thereby influence gene expression and phenotype (Feil & Fraga, ; Price, Peñaherrera, et al, ; Yue, Liu, & He, ). A study of the methylomes in lymphocytes of human SB subjects showed significant overall hypomethylation of SOX18 , a gene not known to associate with NTDs (Rochtus et al, ). This study also showed that addition of sox18 mRNA by injection into zebrafish embryos led to abnormal neural tube closure (Rochtus et al, ).…”
Section: Environmental Factors and Epigenetics Of Human Ntdsmentioning
confidence: 99%
“…A study of the methylomes in lymphocytes of human SB subjects showed significant overall hypomethylation of SOX18 , a gene not known to associate with NTDs (Rochtus et al, ). This study also showed that addition of sox18 mRNA by injection into zebrafish embryos led to abnormal neural tube closure (Rochtus et al, ). In addition, abnormal microRNA profiles were observed in human anencephaly brain tissue (Zhang et al, ) suggesting activity of microRNAs can be modified through post‐transcriptional methylation (Berulava, Rahmann, Rademacher, Klein‐Hitpass, & Horsthemke, ).…”
Section: Environmental Factors and Epigenetics Of Human Ntdsmentioning
confidence: 99%